ANALISIS PENERAPAN ETIKA BISNIS TERHADAP KELANGSUNGAN USAHA PERUSAHAAN DAGANG - Wulandari, Neni Wulandari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Commercial enterprises in Indonesia is a business entity that has a very important contribution to the national economy until now and then. The contribution of trading companies in Indonesia can be seen from the emergence of various kinds of shops, self-service, supermarkets to malls that provide products from suppliers without changing the shape of the product. When running some business, the usage of business ethics is a factor that plays an important role in maintaining business continuity in various sectors, including commercial enterprises or trading companies. Unfortunately, there are still many violations committed by various individuals and business actors in the trade sector which disrupt the stability of the business continuity.